Peningkatan Kesejahteraan Karyawan dan Guru Melalui Pemberdayaan Koperasi Sekolah di Pesantren (Studi Pengabdian Masyarakat di Pesantren SMP, SMA ZAD IQBS) - Satiri, Iwan; Safei, Abdullah; Oki, Alber; Mubarok, Wildan Fata; Haris, Ahmad (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
This community service aims to provide training to individuals to increase social awareness and involvement in militant organizations. This training program is designed to shape participants into socially responsible beings, have sensitivity to social issues, and can contribute positively in the context of militant organizations. The methods used include training sessions, group discussions, simulations, and the formation of joint action projects.